Grain refinement and mechanical properties improvement of additively manufactured Al-Cu alloy through pre-deformation in thermo-mechanical treatment - Zhang, Tao; Chen, Junwen; Gong, Hai; Wu, Yunxin; Chen, Xin (Elsevier, 2024)
Inferior mechanical properties induced by porosity and coarse grains of wire-arc additively manufactured Al-Cu alloy restrict its industrial application. The inter-layer cold rolling, conventional heat treatment (T6) and thermo-mechanical heat treatment (T8) was applied to Al-Cu alloy, and the effect of pre-stretched strain in T8 treatment was investigated. The pre-stretched strain induces equal increments of hardness and YS for both the as-deposited and cold-rolled conditions before aging treatment, while the increments for cold-rolled samples are larger after aging treatment. The cold-rolled sample shows better tensile properties than the as-deposited sample with the same pre-stretched strain in T8 treatment, proving that T8 treatment further increased the strengths compared to the T6 treatment. It shows the best tensile properties with the pre-stretched strain of 5 %, exceeding the properties of 2219-T87 plate. With the increased pre-stretched strain, the density of the θ′ phases significantly increases; while further increase to 10 % pre-stretched strain induces severe coarsening of θ′ phases. Therefore, an optimized pre-stretched strain leads to high-density and tiny dispersed θ′ phases, thus resulting in the best tensile properties. Grain refinement induced by inter-layer cold rolling and uniformly precipitated phases resulted from proper pre-stretched strain both contribute to the strengths enhancement. The strengthening mechanism of hybrid additive manufacturing and inter-layer cold rolling followed by T8 treatment was discussed.
Keywords: 40 Engineering; 4016 Materials Engineering; Materials; 4017 Mechanical engineering; Wire-arc additive manufacture; Inter-layer cold rolling; Pre-stretched strain; Grain refinement; Tensile properties; Strengthening mechanism